MANAJEMEN BIMBINGAN KONSELING DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS - Yusup, Wirastiani Binti (Jurnal Manajemen Pendidikan, 2024)
This research aims to analyze the planning, organizing, implementation and evaluation of guidance and counseling management at SMA Negeri 5 Palangka Raya. Improving the quality of educational services is a target that needs to be strengthened, considering that educational institutions are still not fully able to meet society's needs in recruiting quality graduates. The research method used is a qualitative method; Based on research conducted regarding the management of guidance counseling at SMA Negeri 5 Palangka Raya, it can be concluded: 1) planning guidance counseling is planned through identifying student needs, determining goals and determining resources, 2) organizing guidance counseling is carried out through the division of work tasks for each teacher counseling guidance, organizational structure of counseling guidance, mechanisms for handling problematic students and classification of problematic students, 3) implementation of counseling guidance providing information services, orientation services, responsive services, individual services, group services, case studies, peer guidance using methods modeling and classical and counseling guidance evaluation is carried out through questionnaires or evaluation forms.